Spin Precession and Spin-Charge Conversion in a Strong Rashba Channel at Room Temperature - Kim, Seong Been; Jeon, Jeehoon; Kim, Hyung-jun; Chang, Joonyeon; Koo, Hyun Cheol (KOREAN INST METALS MATERIALS, 2021)
The detection of spin current injected from the ferromagnet source to the semiconductor channel is very challenging due to the low injection efficiency at the interface. Especially, it is difficult to detect the spin precession signal in a strong Rashba system without a signal decay. In a semiconductor system, the spin Hall angle is much larger than the spin injection efficiency, so the spin Hall effect is utilized for room temperature operation of the semiconductor-based Rashba devices. To realize spin transport device induce by the spin-charge and charge-spin conversions, the direct spin Hall effect (DSHE) and the inverse spin Hall effect (ISHE) are adopted, respectively. The spin current is clearly detected up to room temperature and the spin transport signal agrees to the temperature dependence of the Rashba effect. From these spin transport signals, we suggest another option to extract Rashba parameters from cryogenic temperature to room temperature. The both signals of DSHE and ISHE also confirm the Onsager Reciprocity in a Rashba system.